RELATIONSHIP OF NONALCOHOLIC FATTY LIVER DISEASE WITH ANTHROPOMETRIC MEASUREMENT AMONG PATIENTS ATTENDING A TERTIARY CARE HOSPITAL OF NORTHERN INDIA - Siraj, Purnoor; Kohli, Neera; Srivastava, Vinod Kumar; Singh, Shivendra Kumar; Natuq, Shanker Madhav; Mehrotra, Raj (Indian Journal of Community Health, 2013)
Background: Nonalcoholic fatty liver disease (NAFLD) is an increasingly recognized cause of liver disease worldwide. The present study was conducted with the aim to determine the association between anthropometric measurement and incidence of NAFLD among the adult population. Material and Methods: The present cross-sectional study was conducted in the Department of Radiodiagnosis at King Georg’s Medical University, Lucknow. A total of 300 subjects were included by simple random sampling technique. All the subjects aged 20 to 60 years underwent ultrasonography (USG) examination of any part of the body were enrolled in the study. Individuals who have a history of alcohol consumption were excluded from the study. All subjects underwent anthropometric measurement which included height, weight, waist circumference, hip circumference and mid upper arm circumference (MUAC). Body mass index (BMI) and waist hip ratio (WHR) were calculated using the standard formula. Statistical analysis was done by using SPSS 16.0 version.Results: Out of total, 76(25.3%) were found to be diagnosed with NAFLD (95%CI=22.8-27.8) subjects. The cases of NAFLD were significantly higher in males (32.0%) as compared to females (18.7%) (RR=1.17, 95%CI=1.14-2.58, p=0.008). The weight, waist circumference, hip circumference, MUAC, BMI and WHR were significantly (p<0.0001) associated with NAFLD. Likewise, NAFLD was found significantly (p<0.0001) higher among obese and overweight subjects. However, in multivariate logistic regression analysis, sex (adjusted OR=11.30, 95%CI=3.44-37.11, p<0.0001), waist circumference (adjusted OR=1.27, 95%CI=1.56-1.39, p<0.0001), hip circumference (adjusted OR=0.90, 95%CI=0.82-0.99, p=0.04) and BMI (adjusted OR=1.83, 95%CI=1.10-2.20, p=0.001) were significantly associated with NAFLD.Conclusions: It can be concluded that higher anthropometric measurements were significantly associated with NAFLD.